Old Lessons of Risk Assessment and Management from the COVID-19 Pandemics and Individual Infections Dynamics - Romney B Duffey; Enrico Zio (Journal of Risk Analysis and Crisis Response (JRACR), 2021)
Abstract: “Certainty creates strength…Uncertainty creates weakness” (John M Barry “The Great Influenza”, 2005, Penguin Books, p261.). “The theory is this, that it would be appropriate to believe in a proposition until there is a founded reason to suppose its truth. If this view were to become commonly agreed upon, our social lives and our political system would turn out completely changed.” (Bertrand Russell, Sceptical Essays, 1928). “The best way to prevent becoming infected is to avoid being exposed to the virus” (Source: www.astho.org/COVID-19/Q-and-A/). The recent and ongoing COVID-19 pandemic is confirming that our society is vulnerable to global risk and that science and politics are challenged by the associated high uncertainties. This makes a number of old, foundational questions on risk and its management re-emerge. In this paper, specifically for the risk posed by the current pandemic and the infection spreading phenomena driving it, we observe from data and show from theory that there are four characteristic and very human-determined timescales for infection-spread rates. Then, we conclude on the need of putting the humans in the middle/focus of risk, as they are the ones that ultimately take decisions (almost rationally) and live their outcomes. So, we argue the obvious: that is, that for managing risk, it is necessary to realize and accept rationally that risk is not absolute- it is relative and in the uncertainty of the occurrence of different events, some just have more chance of occurring than others (i.e. high versus low chance). To evaluate and compare risks, as a society we should weigh, rank and decide the intertwined balances and resulting inequalities.